Dampak PP 55 Tahun 2022 terhadap Penerimaan Pajak UMKM di KPP Pratama Semarang Barat - Pramesti, Yessy Levina; Oktavia, Vicky; Oktariza, Linda Ayu; Puspitasari, Diana (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study analyzes the impact of Government Regulation No. 55 of 2022 on MSME tax revenue at KPP Pratama Semarang Barat. The background of the study is the significant contribution of MSMEs to the national economy, which is not yet matched by optimal tax compliance. The regulation aims to simplify tax rates, expand exemption facilities, and improve administrative effectiveness. The study employs a descriptive quantitative method using secondary data on Final Income Tax (PPh Final) for MSMEs from 2021–2024, supported by a paired sample t-test. The results show a significant difference with a p-value of 0.022 < 0.05. Average monthly revenue increased from IDR 1.087 billion to IDR 1.196 billion after the policy was implemented, despite a decline in the number of paying taxpayers. This indicates the policy’s effectiveness in boosting tax revenue while reinforcing the fairness principle based on the ability to pay.